Digestible threonine to lysine ratios for meat-type quails - Castro, M. R.; Pinheiro, Sandra Regina Freitas; Oliveira, R. G.; Abreu, L. R.A.; Mota, L. F.M.; Miranda, J. A. (FapUNIFESP (SciELO), 2020)
Three experiments were conducted to estimate the optimal digestible threonine to lysine ratios (Thr:Lys) of meat-type quails during the pre-starter (1 to 7 days), starter (8 to 14 days) and grower I (15 to 21 days) phases. In each experiment, 600 birds were distributed according to a completely randomized experimental design into five treatments, consisting of five dietary Thr:Lys ratios (0.66, 0.71, 0.76, 0.81 and 0.86%), with eight replicates of 15 quails each. Performance parameters and intestinal morphology were evaluated. During the pre-starter phase, feed intake, threonine intake, weight gain, and ileal villus height linearly increased (p<0.01) as dietary digestible Thr:Lys increased. During the starter phase, increasing digestible Thr:Lys ratios had a linear effect (p<0.01) on threonine intake and livability, and linear and quadratic effects (p<0.01) on feed intake. During the grower I phase, increasing digestible Thr:Lys ratios promoted linear increase in threonine intake and feed conversion ratio (p<0.05), and a linear decrease in weight gain. The estimated digestible Thr:Lys ratios recommended for meat-type quails are 0.85, 0.73 and 0.66%, for the pre-starter, starter and grower I phases, respectively.
Keywords: Amino acids; Coturnix coturnix; Ideal protein; Performance